Process Integration of Bioethanol from Sugar Cane and Hydrogen Production (2007)
In this study several alternatives for process integration of bioethanol from sugar cane and hydrogen production were evaluated. Bioethanol was produced above all in the fermentation of sweetened juice from sugar cane, stillage was removed. Stillage and bagasse are the process byproducts. The bioethanol steam reforming is an endothermic catalytic process when vaporized ethanol and steam are fed using a 1:6 molar ratio to reformer with a Ni-catalyst at atmospheric pressure and 350xC. Taking into account the processes properties mentioned above, it is possible to integrate the bioethanol production from sugar cane and its reforming by using byproducts like bagasse and stillage and to produce energy for steam reforming and bioethanol solution concentration by direct firing (for bagasse) or anaerobic digestion to get methane (for stillage).